Molecular detection and isolation of clade Ib monkeypox virus, Canada, November 2024 - James E Strong (Eurosurveillance, 2025)
In November 2024, a case of clade Ib mpox was confirmed in Canada. Here, we describe the events that led to laboratory confirmation of clade Ib monkeypox virus (MPXV) and the public health response. Genomic analysis of the Canadian clade Ib MPXV revealed a number of APOBEC3-related mutations suggesting sustained human-to-human transmission. These findings expand the number of countries with travel-related clade Ib mpox and highlights the continued need for mpox monitoring of potential human adaptations or new transmission patterns.